Memory Reactivation in Healthy Aging: Evidence of Stimulus-Specific Dedifferentiation - St-Laurent, Marie (J Neurosci, 2014)
We investigated how aging affects the neural specificity of mental replay, the act of conjuring up past experiences in one's mind. We used functional magnetic resonance imaging (fMRI) and multivariate pattern analysis to quantify the similarity between brain activity elicited by the perception and memory of complex multimodal stimuli. Young and older human adults viewed and mentally replayed short videos from long-term memory while undergoing fMRI. We identified a wide array of cortical regions involved in visual, auditory, and spatial processing that supported stimulus-specific representation at perception as well as during mental replay. Evidence of age-related dedifferentiation was subtle at perception but more salient during mental replay, and age differences at perception could not account for older adults' reduced neural reactivation specificity. Performance on a post-scan recognition task for video details correlated with neural reactivation in young but not in older adults, indicating that in-scan reactivation benefited post-scan recognition in young adults, but that some older adults may have benefited from alternative rehearsal strategies. Although young adults recalled more details about the video stimuli than older adults on a post-scan recall task, patterns of neural reactivation correlated with post-scan recall in both age groups. These results demonstrate that the mechanisms supporting recall and recollection are linked to accurate neural reactivation in both young and older adults, but that age affects how efficiently these mechanisms can support memory's representational specificity in a way that cannot simply be accounted for by degraded sensory processes.